1993
DOI: 10.1111/j.1651-2227.1993.tb12532.x
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial effusion complicating a percutaneous central venous line in a neonate

Abstract: A premature infant developed pericardial effusion four days after the insertion of a 25-gauge silastic percutaneous central venous catheter. The effusion contained parenteral nutrition fluid and resolved rapidly after withdrawal of the catheter. Pericardial effusion is a potential complication of percutaneous, as well as surgically placed, central venous catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…[1][2][3][4] We found that the use of contrast improves the localisation of long lines on radiography, but that even when contrast is used, precise localisation can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] We found that the use of contrast improves the localisation of long lines on radiography, but that even when contrast is used, precise localisation can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…2 There are a number of case reports of infants who have died or suffered significant morbidity as a consequence of pericardial tamponade. [3][4][5][6] One unit reported that pericardial effusion/tamponade occurred in 3% of inserted lines. 7 Reports in the popular press 8 have also suggested this to be a common complication and that doctors were putting infants lives at unnecessary risk by inserting PLLs.…”
mentioning
confidence: 99%
“…Delayed effusion into either the pleural or pericardial space is an uncommon but well recognized complication of neonatal long line use. Pericardial effusion particularly may be associated with tamponade and infant death 6,7 . The UK Department of Health (DOH) guidelines recommend that the tip of the central line be positioned outside the chambers of the heart 8 although positioning the line tip outside the heart is still associated with complications 9 and migration is a recognized occurrence 10,11 .…”
mentioning
confidence: 99%